2010
DOI: 10.1016/j.yhbeh.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Male Syrian hamsters demonstrate a conditioned place preference for sexual behavior and female chemosensory stimuli

Abstract: Sexual behavior is a natural reward for many rodent species, and it often includes chemosensorydirected components. Chemosensory stimuli themselves may also be rewarding. Conditioned place preference (CPP) is one paradigm frequently used to test the rewarding properties of a range of stimuli. Males and females of several rodent species show a CPP for sexual behavior, however, it is currently unknown whether sexual behavior can induce a CPP in male Syrian hamsters. As male Syrian hamsters are an animal model co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…An additional limitation is that one cannot rule out aggression and sex as unconditioned stimulus in these tasks since rodents will operantly respond to contexts associated with agonistic and sexual interactions [4,17,18]. However, despite the lack of formal assessment, observers noted no instances of sexual or aggressive interactions during the manually-scored conditioning sessions.…”
Section: 1 Discussionmentioning
confidence: 99%
“…An additional limitation is that one cannot rule out aggression and sex as unconditioned stimulus in these tasks since rodents will operantly respond to contexts associated with agonistic and sexual interactions [4,17,18]. However, despite the lack of formal assessment, observers noted no instances of sexual or aggressive interactions during the manually-scored conditioning sessions.…”
Section: 1 Discussionmentioning
confidence: 99%
“…We found that sexually naïve adult male hamsters form a CPP to female pheromones alone, which indicates that pheromones are an unconditioned reward in adulthood (Bell, Meerts, & Sisk, 2010). In contrast, juvenile male hamsters fail to form a CPP to female pheromones, which demonstrates that pheromones are not an unconditioned reward in preadolescent males, consistent with our hypothesis that the rewarding properties of female pheromones are acquired over adolescent development (Bell, De Lorme, Figueira, Kashy, & Sisk, 2012).…”
Section: Social Rewardmentioning
confidence: 93%
“…The control animals were used to confirm that preference scores do not change over the period of exposure to the two different compartments in the absence of conditioning. This biased assignment approach to CPP has been used previously for both sexual and drug rewards (Paredes and Alonso, 1997, Pierman et al, 2006, Dominguez-Salazar et al, 2008, Camacho et al, 2009, Meerts and Clark, 2009, Bell et al, 2010). The CPP apparatus was cleaned thoroughly with 25% ethanol following each Test and conditioning session between animals, and 75% ethanol after each S day.…”
Section: Methodsmentioning
confidence: 99%
“…Either a clean or vaginal secretion-containing Eppendorf tube was taped to the top of the back wall of each respective compartment, out of reach of the male. The purpose of the two modes of vaginal secretions delivery was to ensure exposure to both volatile and non-volatile components, as both are important and potentially have different roles in male sexual behavior (as discussed in Bell et al, 2010). Control animals received blank oil and empty tubes on all sessions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation